Social Work Continuing Education: A Statewide Case Study. Issue 4 (7th August 2016) - Gianino, Mark; Ruth, Betty J.; Miyake Geron, Scott
ABSTRACT: This article presents findings from a 2013 qualitative study of social work continuing education (CE) in Massachusetts. Eleven focus groups were conducted with 75 participants from key stakeholder groups: practitioners, educators, licensing board members, and agency administrators. Although positive perspectives surfaced—such as diversity of CE options—thematic analysis nonetheless reflected considerable frustration with the current system. CE concerns included lack of access, cost, missing CE content areas, quality control issues, and lack of employer support. Participants also noted the need for enhanced transfer of CE-derived knowledge and skills in the workplace. Greater attention to this crucial aspect of professional development is therefore needed.